Comparison of Knowledge of Obsessive-Compulsive Behavior between Counseling Students and School Administration Students - Foster, Sandy ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
Obsessive-compulsive adolescence behavior in the classroom environment can be disruptive, affecting the teacher and other students. Certain personality traits of the obsessive-compulsive are obvious, while other symptoms are frequently misdiagnosed. As school staff are often the first step in the primary diagnosis process, the purpose of this study is to document and compare knowledge and understanding of symptomology and traits between the School Administration and Counseling disciplines in the area of obsessive-compulsive behaviors. Data drawn from a Likert Scale questionnaire administered to students (N=25) in the School Administration and the Licensed Professional Counseling programs at Sam Houston State University offer a comparative analysis between knowledge and understanding of obsessive-compulsive behavior in these two fields of study. Questionnaires were given to assess the familiarity with, and recognition of the types of obsessive-compulsive behavior. Questions relating to underlying cause, prevalence between gender, age at onset, knowledge of testing instruments, and the most effective type of intervention were asked, in an attempt to discern any differences in knowledge between the fields. No significant difference was found. Appended are a letter to participants, the questionnaire, and nine tables presenting raw data and statistical results. (JBJ)
ERIC Note: Masters Research Paper, Sam Houston State University. The first three tables contain broken print.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Education; Behavior Disorders; Clinical Diagnosis; Counselor Training; Educational Administration; Educational Diagnosis; Elementary Secondary Education; Higher Education; Knowledge Level; Obsessive Compulsive Behavior; Dissertations/Theses.; Tests/Questionnaires.